2022
DOI: 10.7324/japs.2022.120903
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of soluble recombinant Thermus thermophilus (Tth) DNA polymerase in Escherichia coli BL21(DE3) using an MBP fusion tag as a solubility enhancer

Abstract: Tth DNA polymerase is a thermostable enzyme derived from Thermus thermophilus and acts as a DNA polymerase and reverse transcriptase. Escherichia coli is used for large-scale enzyme production because of its cost-effectiveness, rapid growth, and increased recombinant protein expression, but inclusion bodies can be formed during intracellular protein expression, so the maltose-binding protein (MBP) tag was used to improve the expression of soluble protein. The Tth DNA polymerase gene was optimized to have a cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Secondly, MBP's role is transient, temporarily preventing improper folding of the recombinant protein until spontaneous folding occurs with the assistance of endogenous chaperones (Bhatwa et al, 2021;Paraskevopoulou & Falcone, 2018). Studies by Maksum et al, (2022) and Fang et al, (2018) have reported that overexpressing heterologous recombinant proteins in the E. coli BL21(DE3) host, in conjunction with MBP sequences in the recombinant plasmid construct, significantly enhances solubility and stability of protein expression compared to traditional overexpression methods without MBP insertion.…”
Section: Fusion Maltose-binding Protein (Mbp) On Pga Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, MBP's role is transient, temporarily preventing improper folding of the recombinant protein until spontaneous folding occurs with the assistance of endogenous chaperones (Bhatwa et al, 2021;Paraskevopoulou & Falcone, 2018). Studies by Maksum et al, (2022) and Fang et al, (2018) have reported that overexpressing heterologous recombinant proteins in the E. coli BL21(DE3) host, in conjunction with MBP sequences in the recombinant plasmid construct, significantly enhances solubility and stability of protein expression compared to traditional overexpression methods without MBP insertion.…”
Section: Fusion Maltose-binding Protein (Mbp) On Pga Expressionmentioning
confidence: 99%
“…Proteins folding incorrectly may interact with each other, rendering the protein biologically inactive. This issue arises due to the reducing conditions within the cytosol of E. coli and the limited availability of chaperone proteins, which fail to cope with the high levels of recombinant protein expression (Maksum et al, 2022). The challenge of ensuring proper protein conformation during expression in the host is critical in achieving substantial bioactive PGA recombinant protein mass.…”
Section: Introductionmentioning
confidence: 99%